Recent Publications (Quarterly Journal of Economics, 1966)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 80, Issue 3, August 1966, Pages 493–501, https://doi.org/10.1093/qje/80.3.493 Published: 01 August 1966